The PENGARUH MULTIMEDIA INTERAKTIF BERBASIS PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR KOGNITIF DAN SIKAP PEDULI LINGKUNGAN SISWA KELAS IV SD NEGERI 51 SELUMA: PENGARUH MULTIMEDIA INTERAKTIF BERBASIS PROBLEM BASED LEARNING - Dwi Jayanti, Lofty; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The purpose of this study was to analyze the effect of interactive multimedia based on Problem Based Learning on Cognitive Learning outcomes and Students' Environmental Care Attitudes. The type of research used is quasy experimental research using Nonequivalent control group design. The type of data used is quantitative data, namely using test instruments and questionnaire sheets. Based on the results of hypothesis testing, Fcount> Ftable and sign value <0.000. The N-Gain test on the experimental class test sheet of 72.81% is included in the moderately effective category and in the control class of 39.94% is included in the ineffective category. In the N-Gain test, the experimental class questionnaire sheet of 63.21% was included in the moderately effective category. While the N-Gain score of the control class of 50.22% is included in the less effective category. It can be concluded that interactive multimedia based on Problem Based Learning has a significant effect on cognitive learning outcomes and students' environmental care attitudes.